2018
DOI: 10.1158/0008-5472.can-17-1346
|View full text |Cite
|
Sign up to set email alerts
|

PHD3 Controls Lung Cancer Metastasis and Resistance to EGFR Inhibitors through TGFα

Abstract: Disclosure of Potential Conflicts of InterestNo potential conflicts of interest were disclosed.Research. Author manuscripts have been peer reviewed and accepted for publication but have not yet been edited. Author Manuscript Published OnlineFirst on January 16, 2018; DOI: 10.1158/0008-5472.CAN-17- SignificanceThis study links the oxygen sensor PHD3 to metastasis and drug resistance in cancer, with implications for therapeutic improvement by targeting this system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…For colony formation assay, cells were exposed to CT-707 under normoxia or hypoxia for 24 hours, then trypsinized and re-plated at a density of 500 living cells/well in six-well plates. Two weeks later, cells were stained with crystal violet solution and the number of colonies having more than 50 cells were counted (10). For apoptosis detection, cells treated with CT-707 were analyzed after staining with PI solution (#ZF-50-0001; Multi Sciences, Ltd.), on a FACS Calibur cytometer (Becton Dickinson; ref.…”
Section: Sulforhodamine B Assay Colony Formation Assay and Flow Cytmentioning
confidence: 99%
“…For colony formation assay, cells were exposed to CT-707 under normoxia or hypoxia for 24 hours, then trypsinized and re-plated at a density of 500 living cells/well in six-well plates. Two weeks later, cells were stained with crystal violet solution and the number of colonies having more than 50 cells were counted (10). For apoptosis detection, cells treated with CT-707 were analyzed after staining with PI solution (#ZF-50-0001; Multi Sciences, Ltd.), on a FACS Calibur cytometer (Becton Dickinson; ref.…”
Section: Sulforhodamine B Assay Colony Formation Assay and Flow Cytmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer-related death worldwide, with a propensity for distant metastasis. Better understanding of the molecular events that regulate the development of lung cancer metastasis and biomarkers that predict which patients will experience metastasis are needed to improve survival rates (24). It has been reported that cancer cells secrete EVs that can be easily isolated from various body fluids (25) and which contain cancer-specific contents.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has suggested that miR-152-3p suppressed PC cells migration and invasion by downregulating TGF-α [14]. The aberrant expression of TGF-α and TGF-α-induced signaling was involved in the progression and metastasis of various carcinomas [25][26][27]. TGF-α was found to bind to EGFR ligands and activate EGFR by inducing EGFR tyrosine autophosphorylation [28].…”
Section: Discussionmentioning
confidence: 99%